Influence of the initial acidification step on biogas production and composition. (7th March 2014) - Dirnena, Ilze; Dimanta, Ilze; Gruduls, Arturs; Kleperis, Janis; Elferts, Didzis; Nikolajeva, Vizma
Abstract Laboratory‐scale experiments were carried out to evaluate the effect of initial acidification of feedstock consisting of different components on biogas production and composition. Feedstock containing different agricultural wastes, biomass, and microorganisms was collected from five full‐scale biogas plants. Two continuously stirred tank reactors were used. The fermentation temperature was 37 °C. The pH value was adjusted to 6.0 in the first reactor at the beginning of the experiment, and an initial pH value of 7.0 was implemented after 48 H. The second reactor was used as a control reactor with a constant pH of 7.0. The experiment lasted a total of 7 days. In the reactors, the gas phase was dominated by CH4, CO2, and N2. The results showed that acidification increased biogas and carbon dioxide production in five cases, increased methane production and reduced nitrogen production in four cases, and reduced methane content in biogas in four of five cases. Only feedstock composed of 74% of different manures and 26% of plant material reduced the production of methane and increased the production of nitrogen after acidification. Other feedstock contained 47% to 96% plant material. An initial pH value of 6 could be recommended for mesophilic single‐phase methanogenesis with a prevalence of plant material.